2019
DOI: 10.1186/s12889-019-6716-2
|View full text |Cite
|
Sign up to set email alerts
|

Noncommunicable disease burden among HIV patients in care: a national retrospective longitudinal analysis of HIV-treatment outcomes in Kenya, 2003-2013

Abstract: Background Over the last decade, the Kenyan HIV treatment program has grown exponentially, with improved survival among people living with HIV (PLHIV). In the same period, noncommunicable diseases (NCDs) have become a leading contributor to disease burden. We sought to characterize the burden of four major NCDs (cardiovascular diseases, cancer, chronic respiratory diseases and diabetes mellitus) among adult PLHIV in Kenya. Methods We conducted a nationally representativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 32 publications
9
69
5
1
Order By: Relevance
“…There is need for deepening the capacity of suppliers for managing the dramatic increase in demand or the sheer volumes of ART medicines to be dispensed occasioned by DSD implementations such as multimonth scripting [7]. Our findings point to the need for harmonizing appointment spacing in HIV care with the management of other co-morbidities such as diabetes and hypertension [36], [37]. We found that older patients (50 years and above) who had well-controlled sugar levels or blood pressure and were also stable on ART were still required to make monthly clinic visits regardless of the DSD provision of 3-monthly visits.…”
Section: Study Implications For Countries With Similar Setting As Ugandamentioning
confidence: 83%
See 1 more Smart Citation
“…There is need for deepening the capacity of suppliers for managing the dramatic increase in demand or the sheer volumes of ART medicines to be dispensed occasioned by DSD implementations such as multimonth scripting [7]. Our findings point to the need for harmonizing appointment spacing in HIV care with the management of other co-morbidities such as diabetes and hypertension [36], [37]. We found that older patients (50 years and above) who had well-controlled sugar levels or blood pressure and were also stable on ART were still required to make monthly clinic visits regardless of the DSD provision of 3-monthly visits.…”
Section: Study Implications For Countries With Similar Setting As Ugandamentioning
confidence: 83%
“…We found that older patients (50 years and above) who had well-controlled sugar levels or blood pressure and were also stable on ART were still required to make monthly clinic visits regardless of the DSD provision of 3-monthly visits. This calls for the integrated management of HIV and other comorbidities that is becoming increasingly important priority due to ageing cohorts of clients and the need to revisit treatment guidelines even in non-HIV services [36], [37], [45].…”
Section: Study Implications For Countries With Similar Setting As Ugandamentioning
confidence: 99%
“…There is need for deepening the capacity of suppliers for managing the dramatic increase in demand or the sheer volumes of ART medicines to be dispensed occasioned by DSD implementations such as multi-month scripting [7,41]. Our findings point to the need for harmonizing appointment spacing in HIV care with the management of other co-morbidities such as diabetes and hypertension [42,43]. We found that older patients (50 years and above) who had well-controlled sugar levels or blood pressure and were also stable on ART were still required to make monthly clinic visits regardless of the DSD provision of 3-monthly visits.…”
Section: Study Implications For Countries With Similar Setting As Ugandamentioning
confidence: 84%
“…A study in the United States reported that HIV-infected adults had a 1.5 fold increased risk of having a heart attack [33] and were nearly 50% more likely to have received a diagnosis of chronic obstructive pulmonary disease (COPD) compared to demographically and behaviourally similar uninfected controls [34]. Other NCDs more commonly reported in HIV-infected compared to uninfected persons include cardiovascular events [35], hypertension [36,37], osteoporosis [38], renal impairment [39], diabetes mellitus [40], and depression and neurocognitive disorders [41].…”
Section: The Rise Of Multimorbidity In the Context Of Hivmentioning
confidence: 99%